2004
DOI: 10.1097/00024720-200404000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Effect of Lumbar Spine Fusion on the Superior Adjacent Intervertebral Disk in the Presence of Disk Degeneration, Using the Three-Dimensional Finite Element Method

Abstract: The purpose of this study was to analyze the effect of lumbar spine fusion on the superior adjacent intervertebral disk in the context of disk degeneration, using a nonlinear three-dimensional finite element method. Detailed L3-L5 motion segment models of normal and degenerated intervertebral disks were developed. In fusion models, L4-L5 was fixed by either posterolateral fusion or posterior lumbar interbody fusion (PLIF). Various loading conditions such as compression loading, compression loading plus flexion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(33 citation statements)
references
References 19 publications
0
32
0
1
Order By: Relevance
“…This has been proven by an observed increase in the intradiscal pressures and segmental motion at the adjacent segment after lumbar arthrodesis. 13,14 Through this alteration, it seems that lumbar arthrodesis contributes to the degeneration of the adjacent segments. 15 However, an alternative theory claims that ASD follows a natural degenerative course in patients who are predisposed.…”
Section: Discussionmentioning
confidence: 99%
“…This has been proven by an observed increase in the intradiscal pressures and segmental motion at the adjacent segment after lumbar arthrodesis. 13,14 Through this alteration, it seems that lumbar arthrodesis contributes to the degeneration of the adjacent segments. 15 However, an alternative theory claims that ASD follows a natural degenerative course in patients who are predisposed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suspected that the stiffness of the instrumented levels relates directly to increased stress on the cranial adjacent segment and facet joints [10,11]. The increased load over time leads to segmental hypermobility, facet joint hypertrophy, osteophyte formation, and spinal stenosis [12].…”
Section: Introductionmentioning
confidence: 99%
“…In 1988, Geol took advantage of CT geometrical scanning to reconstruct the human digital model, but the meshing accuracy of CT-based digitized human anatomical model was very low, it was difficult to ensure the accuracy of model solution results [26]. With the continuous development of CT and 3D reconstruction, especially the technological innovation of 32-row and over, multi-slice spiral CT and dual-source CT, the CT bone 3D imagingresolution keeps increasing, not only the resolution of field of view (FOV) has been significantly improved, the slice thickness could reach the mm level, providing the possibility towards the digitized reconstruction of CT-based 3D data [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the cell delivery-based bone repairing technology, which is currently available in clinic, is still limited to the repairing of focal lesions [5]. In recent years, the high polymer-inorganic substances has become the hotspot in the bone tissue engineering (BTE) research because of its biodegradability and easy 3D processing [6], Alothman et al [7] found that the composite of high-density polyethylene (HDPE)-hydroxyapatite (HA) exhibited the tensile strength as up to [22][23][24][25][26][27][28] MPa and the changes of HA content might adjust the characteristic of composite; Zein et al [8] found that the compressive strength of poly-e-caprolactone (PCL) could reach 4-77 MPa, and the yield strength cold reach 0.4-3.6 MPa when the pore size was 160-700 mm and the porosity was 48-77 %, which was much more suitable for the requirements of BTE.…”
Section: Introductionmentioning
confidence: 99%